Presence of the rabies virus in non-hematophagous bats in Mexico - Calderón-Patrón, Jaime Manuel; Cornejo-Latorre, Cristian; Rosas Pacheco, Luis Fernando; López González, Carlos Alberto (Ecosistemas y Recursos Agropecuarios, 2024)
The presence of the rabies virus and antibodyes in bats from the Americas is mainly associated with hematophagous species; however, this virus has also been detected with low frequency in bats with other feeding habits. The same thing happens in Mexico, although there is no updated information on the species that have been infected by this virus. Due to the public health implications of the subject, in this study we explore how the presence of the rabies virus is related to eating habits, the family to which they belong, the size of the distribution area and the type of refuge used by bats. Based on a review of the scientific literature published from 1954 to 2015, seven families, 24 genera, and 40 species of non-hematophagous bats that have been detected with rabies virus in Mexico. Most are insectivorous (63%) and belong to the Phyllostomidae and Vespertilionidae families (68%). The presence of rabies is positively and significantly related to the number of species per family (r = 0.9, p < 0.005) and type of feeding habit (r = 0.97, p < 0.002) but is not related to the size of its distribution area (r = 0.2, p = 0.2). Cases of rabies in non-hematophagous species in Mexico are rare, and do not represent a risk of transmission to humans.